ANALISIS KONSEP AUDIT SOSIAL SEBAGAI STANDAR EVALUASI KINERJA ENTITAS DALAM MELAKUKAN CSR (CORPORATE SOCIAL RESPONSIBILITY) - IKAYANTI, (Jurnal Akuntansi AKUNESA, 2014)
Corporate Social Responsibility (CSR) now is being popular because ofIndonesian’s goverment regulate that every company who use natural resourcesmust do it. In fact there is no standard or instrument that can measure or evaluateCSR. This journal discuss about instrument which can use to evaluate CSR, socialaudit. Analyzing previous research and some literature are the method to find outthe solution. Social audit can used to performance measurement of CSR. Internalauditor make the report of social audit which can be the foundation to evaluatecompany’s performance with the result that the company’s progressKeywords: Social audit, evaluate, performance.